English Lecturer’s Preparation in Teaching TOEIC: a Case Study of the Economic And Business Study Program - Tira Nur Fitria (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2025)
This study describes the English lecturer’s preparation in teaching the Test of English for International Communication (TOEIC) to students of the Economic and Business Study Program at ITB AAS Indonesia. Employing a descriptive qualitative approach with a case study design, the research focuses on one English lecturer, with data collected through documentation analysis of institutional instructional materials. Data were analyzed using data reduction, data display, and conclusion drawing and verification. The findings indicate that TOEIC instruction is systematically designed and implemented over 14 meetings, covering two main sections: Listening and Reading. The Listening section aims to develop students’ test-taking strategies for Parts 1 to 4, while the Reading section focuses on strategies for Parts 5 to 7. The lecturer structures the early meetings around Listening Comprehension, including photographs, questions and responses, short conversations, and talks, followed by sessions on tips, review, and practice. Subsequent meetings emphasize Reading Comprehension, addressing incomplete sentences, text completion, and single and multiple passages, also supported by tips, review, and practice activities. In addition, TOEIC preparation is strengthened through guided independent learning using online resources such as the official ETS website, Exam English, and Practice the TOEIC Test, which help students become familiar with the test format and enhance their English proficiency. Overall, these findings demonstrate that systematic lecturer preparation and the integration of structured classroom instruction with independent learning resources contribute to more focused and relevant TOEIC preparation for economics and business students. This approach supports the development of practical English skills aligned with workplace communication needs and increases students’ readiness to face standardized English proficiency tests